2015
DOI: 10.1007/s10126-015-9614-3
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Metabolites and Bacteriolytic Enzymes Produced by Bacillus pumilus During Bacteriolysis of Arthrobacter citreus

Abstract: The marine isolate Bacillus pumilus SBUG 1800 is able to lyse living cells of Arthrobacter citreus on solid media as well as pasteurized A. citreus cells in liquid mineral salt medium. The cultivation of B. pumilus in the presence of pasteurized A. citreus is accompanied by an enhanced production of 2,5-diketopiperazines (DKPs). DKPs inhibit bacterial growth, but do not seem to cause bacteriolysis. This study shows that B. pumilus also lyses living cells of A. citreus in co-culture experiments as an intraguild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Among these lipopeptides, pumilacidin was a novel lipopeptide similar to surfactin and was first characterized from Bacillus pumilus (26). Although there have been only a few studies of pumilacidin after its discovery, it has been reported to possess different functions, such as antiviral (26), antifungal (34), and antibacterial (36) applications. To date, none of the lipopeptides have been reported to possess antimotility activity.…”
Section: Discussionmentioning
confidence: 99%
“…Among these lipopeptides, pumilacidin was a novel lipopeptide similar to surfactin and was first characterized from Bacillus pumilus (26). Although there have been only a few studies of pumilacidin after its discovery, it has been reported to possess different functions, such as antiviral (26), antifungal (34), and antibacterial (36) applications. To date, none of the lipopeptides have been reported to possess antimotility activity.…”
Section: Discussionmentioning
confidence: 99%
“…10 Pumilacidins display a broad spectrum of biological activities, such as antiviral activity against herpes simplex virus type 1, antiulcer activity, 10 antifungal activity, 12 antibacterial activity against Staphylococcus aureus and S. epidermis, 14,21 cell lysis. 16 Recently it was demonstrated that pumilacidins A and C inhibit the growth of malarial parasites in vitro. 20 In this work, the antimicrobial activity of all isolated compounds was evaluated against Pseudomonas aeruginosa, Escherichia coli, methicillin resistant Staphylococcus aureus, Bacillus subtilis and Candida albicans, but none of them showed antimicrobial activity at the maximum concentration tested (1000 μg mL -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This class of lipopeptides are often detected in Bacillus pumilus culture, usually by using liquid chromatography-mass spectrometry (LC-MS) techniques. [11][12][13][14][15][16] The potential of Bacillus species as promising sources of structurally diverse and bioactive compounds led us to investigate the chemical composition and biological activity of the sediment-derived bacterium Bacillus sp. 4040 isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactins are reported to have several biological effects such as antifungal, antibacterial, anti-inflammatory, and antiparasitic activities ( Plasmodium ) [ 6 , 7 , 8 , 9 , 10 , 15 , 16 , 17 , 18 ]. In a study testing the anti- Plasmodium activity, the authors showed that surfactins from Bacillus licheniformis BC98 were able to inhibit the activity of the Sir2 enzyme [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surfactins are cyclic lipopeptides that consist of a heptapeptide backbone and one β-hydroxyl fatty acid with variable chain lengths (12–16 carbons) produced by members of the Bacillus genus [ 1 , 2 , 3 , 4 , 5 ]. These compounds display a broad spectrum of biological activities, such as antibacterial [ 6 , 7 ], antifungal [ 8 , 9 , 10 ], antiviral and anti-ulcer [ 11 ], hemolytic [ 12 ], antitumor [ 13 ], anti-mycoplasma [ 14 ], anti-inflammatory [ 15 , 16 , 17 , 18 ], and insecticidal [ 19 ], and they have neuroprotective effects [ 20 ] among other properties that make them promising for industry, biotechnology, and pharmacy [ 21 ]. Pumilacidins are a variant of the surfactin family that consist of a β-hydroxy fatty acid, l -glutamic acid, l -leucine, d -leucine, l -leucine, l -aspartic acid, d -leucine, and l -isoleucine (or l -valine), and they exhibit antiviral activity against herpes simplex virus type 1 and inhibitory activity against hog gastric H + , K + -ATPase [ 11 ], and recently, antibacterial activity against Staphylococcus aureus [ 22 ].…”
Section: Introductionmentioning
confidence: 99%